Enhancing the knowledge spillover through the formation of the oligocentric national innovation system - Yuri V. Preobrazhenskiy; Anna A. Firsova (Indonesian Journal of Geography, 2020)
The processes of spatial polarization of economic activity and potential of regional innovation systems are an important area of study of the innovation transfer in the global world. The present study continues the scientific discussion on the ratio of concentration and uniform innovation development. The objective of the study is to analyze indicators of spatial concentration of innovation activity and the knowledge spillover between regions in the national innovation system. The main methods are the application of the Herfindal-Hirschman index, as well as cartographic analysis. The analysis of the concentration degree of the following indicators of innovation activity was carried out: patents, developed and used advanced technologies, R&D costs, output of innovative products in these regions of Russia using the Herfindal-Hirschman index. A graphical method was used to identify the main regions of the centers and peripheries, and a map of fragmentation of the country's innovative cores was constructed. The results of the study confirmed the hypothesis of a greater spatial concentration of knowledge in comparison with the release of innovative products. Analysis of potential knowledge spillover between regions showed that the indicators associated with the generation of knowledge, focused on the Russian regions is significantly stronger than the indicators for innovative output: spatial concentration of developed advanced technologies are higher than that used advanced technologies, and the concentration of expenditure on technological innovations ahead of the release of innovative products. This indicates an unbalanced nature of the effects of the innovative spillover, when the use of technologies is more widespread than their development and implementation. Recommendations are also presented on a more efficient organization of the innovation space and on the transition from a monocentric model of organizing a socio-economic space to an oligocentric model to reduce excessive polarization and increase the efficiency of knowledge spillover.